Implications of seasonal leukocyte blood formula fluctuations in stallions for breeding management - Nezalenova Anastasia; Shirokova Olga; Frolova Natalia; Romanova Alina; Borodkina Elena; Ustyantseva Anna (BIO Web of Conferences)
The influence of seasons of the year on the leukocyte blood formula parameters in stallions was studied. The study involved 14 stallions of different breeds; the average age of animals was 9.8 ± 2.0 years. It was found that the composition of leukocytic formula in stallions can change in different seasons of the year. We observed an increase in the number of segmented neutrophils in the studied stallions in spring and summer compared to the fall-winter period. In spring and summer periods we observed a decrease in the number of lymphocytes in the blood compared to the fall and winter periods. We found an increase in the number of eosinophils in the blood in summer and fall. The number of segmented neutrophils and lymphocytes in the blood of stallions by 13% and 12%, respectively, depended on the season of the year (p<0.05).